UTILIZATION PATTERNS OF NON-TIMBER FOREST PRODUCTS AMONG RURAL HOUSEHOLDS IN OSUN STATE, NIGERIA - Ogunsina, B.I.; Olorunfemi, O.E.; Adefila, O. A.; Adara, C.T.; Uyamasi, I. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the utilization patterns of Non-Timber Forest Products (NTFPs) among rural households in Osun State, Nigeria. Forest resources play a crucial role in enhancing household income, food security, and livelihood sustainability, especially in developing countries. Despite their importance, NTFPs are often undervalued in national development planning. The study specifically sought to assess the socio-economic characteristics of rural households and identify the major NTFPs utilized in the study area. A multistage sampling technique was employed to select sixty (60) respondents from six communities across three randomly chosen Local Government Areas. Data were collected using a well-structured interview schedule and analysed using descriptive statistics such as frequency, percentage, and mean values. Findings revealed that most respondents were within the active age range of 47–57 years (51.7%), with the majority being married (85.0%) and possessing household sizes of 1–5 persons. Only 15.0% had no formal education, implying high literacy levels that could enhance willingness to adopt sustainable forest-use practices. Results further showed that fuelwood X = 2.93), tree poles and bamboo (mean = 2.92 each), medicinal plants (mean = 2.88), teal leaves (X = 2.81), and seasonal vegetables (X = 2.83) were the most highly utilized NTFPs. These products were used for both income generation and household consumption, underscoring their significance in rural livelihoods.The study concludes that NTFPs make substantial contributions to economic resilience and food security in the study area. It recommends that policymakers and stakeholders integrate NTFPs into forest conservation and rural development strategies to ensure sustainable management and continuous availability of forest resources.